Late Pleistocene submarine terraces in the Eastern Mediterranean, central Lebanon, Byblos: Revealing their formation time frame through modeling. (20th November 2022) - Georgiou, N.; Geraga, M.; Francis-Allouche, M.; Christodoulou, D.; Stocchi, P.; Fakiris, E.; Dimas, X.; Zoura, D.; Iatrou, M.; Papatheodorou, G.
Abstract: Important evidence related to sea-level fluctuation, human evolution and dispersal that took place onshore during the Late Pleistocene and Holocene eras, are currently found underwater due to the sea-level rise. In this study, we present submarine relative paleo sea-level indicators found offshore the Lebanese coastline, at large from the prominent ancient city of Byblos. Two different submarine erosional terrace sequences were identified at depths ranging from −40 to −25m ("distant" sequence) and −11 to 0m ("nearshore" sequence) below present sea level, by using a combination of high-resolution geophysical means and terrain data analysis techniques. In the absence of datings, a model that uses relative sea-level curves for different uplift rates and examines the terraces' formation for various cliff retreat rates (derived from literature and on-field GPS measurements) was built. This model indicates the most possible time frames of the submarine terraces' (STs) formation. The "nearshore" terrace sequence is suggested to have originally been formed during Marine Isotope Stage 5a (MIS5a) sea-level highstand, while it was possibly re-flattened during the first MIS1 sea-level slowdown (8–6 ka BP). The "distant" sequence formation is placed between the MIS4 to MIS3 transition (∼62–50 ka BP), and during MIS3 sea-level highstands within 45–35 ka BP. It was also found that a long-term uplift rate of 0.28–0.37 mm/a and cliff retreat rate of 0.03–0.09 m/a best fit our data and existing onshore relative sea-level indicators. The formation of the STs at this time was further supported by chronologically intercurrent uplifting events that facilitated their formation and preservation. Finally, our model supports recent ice-sheet reconstructions related to higher MIS3 values since sea-level curves that were tested for this scenario (eustatically reaching up to −37/−38m depth), proved more successful in the formation of the "distant" sequence. Graphical abstract: Image 1